2018
DOI: 10.1177/0361198118777080
|View full text |Cite
|
Sign up to set email alerts
|

Biking to Ride: Investigating the Challenges and Barriers of Integrating Cycling with Regional Rail Transit

Abstract: Integrating bicycling with public transport can potentially benefit cyclists and transit operators. Successfully coordinating these transport modes, however, can be a difficult task when so little is known about the social and environmental barriers to this type of multimodal travel in the North American context. Using data derived from a survey of regional train service patrons in the Greater Toronto and Hamilton regions of Ontario, Canada, this study examines the challenges faced by those who cycle to/from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…By applying a few simple rules, we have found that most of the top O-D pairs in BSS provide first-and last-mile connections between transportation hubs and residence neighborhoods in DC. Such multimodal connections indicate a complementary relationship (Barber and Starrett, 2018) between bikeshare and transit that is potentially beneficial to cyclists and operators (Ravensbergen, 2018). The results in Fig.10 indicate that bike trip time has low variations between O-D pairs, and the parametric models of O-D trip time between BSS stations could be adopted and used for real-time intermodal planning (Griffin and Sener, 2016) by road users.…”
Section: Contributions On Travel Patterns and Characteristicsmentioning
confidence: 91%
“…By applying a few simple rules, we have found that most of the top O-D pairs in BSS provide first-and last-mile connections between transportation hubs and residence neighborhoods in DC. Such multimodal connections indicate a complementary relationship (Barber and Starrett, 2018) between bikeshare and transit that is potentially beneficial to cyclists and operators (Ravensbergen, 2018). The results in Fig.10 indicate that bike trip time has low variations between O-D pairs, and the parametric models of O-D trip time between BSS stations could be adopted and used for real-time intermodal planning (Griffin and Sener, 2016) by road users.…”
Section: Contributions On Travel Patterns and Characteristicsmentioning
confidence: 91%
“…Across North American regions, an emphasis on cycling to solve this first/last mile challenge is a much discussed yet under-researched topic ( 3 , 7 , 8 ). Prior research shows that in the GTHA, 22% of all trips to a GO Train station are between 1 and 5 Km in length and could potentially be cycled ( 9 ).…”
mentioning
confidence: 99%
“…Getting sweaty and the lack of showers at destination have often been identified as major barriers for utilitarian cycling (26)(27)(28). This hypothesis is further supported by a survey conducted in the Greater Toronto Area showing that 38% of rail riders do not want to combine rail and bike because they do not want to be sweaty during their train ride (29). Since the majority of BMB users only make one BMB trip by day when this trip chain is used, their return trip in the evening is either made only by Bixi or with a combination of public transport and a single Bixi trip.…”
Section: Discussionmentioning
confidence: 90%